1993
DOI: 10.1159/000126375
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Potentiates Serotonin-2 Receptor-Mediated Intracellular Ca<sup>2+</sup> Mobilization in C6 Glioma Cells

Abstract: Serotonin (5-hydroxytryptamine; 5-HT) caused a transient increase in intracellular Ca2+ in C6BU-1 glioma cells in a concentration-dependent manner; half maximally at 73 nM. The 5-HT2 agonist 1-(4-iodo-2,5-dimethoxyphenyl)-2-aminopropane also increased the levels of intracellular Ca2+ whereas the 5-HTιc agonist l-(3-chlorophenyl)piperazine and 5-HT1a agonist 8-hydroxy-2-(di-n-propylamino)tetralin were completely ineffective. Ketanserin and spiperone blocked the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…2,27,28 Here, we report the rapid nongenomic effect of the synthetic GC, DM, on the early signaling events typically initiated by TCR ligation in T cells. Previous studies have reported that DM or GC treatment can inhibit TCR-mediated signaling responses, [28][29][30][31][32] including Lck, Fyn, and ZAP70 phosphorylation within activated T cells. 7 We have observed similar effects on activated T cells where DM treatment resulted in decreased Lck phosphorylation in this manuscript.…”
Section: Discussionmentioning
confidence: 97%
“…2,27,28 Here, we report the rapid nongenomic effect of the synthetic GC, DM, on the early signaling events typically initiated by TCR ligation in T cells. Previous studies have reported that DM or GC treatment can inhibit TCR-mediated signaling responses, [28][29][30][31][32] including Lck, Fyn, and ZAP70 phosphorylation within activated T cells. 7 We have observed similar effects on activated T cells where DM treatment resulted in decreased Lck phosphorylation in this manuscript.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, on one hand fluoride (5-10 mM, 95-190 mg/l) has been observed to inhibit directly, in rat skeletal muscle, the tyrosine kinase activity of the insulin receptor [79], and aluminum fluoride (3 mM, 57 mg/l fluoride) inhibits phospholipase D (PLD) in rat submandibular cells by a G protein-independent mechanism, which could be a regulatory protein of PLD or PLD itself [80]. On the other hand, in C6 rat glioma cells, sodium fluoride (10 mM, 190 mg/l fluoride) activated Gs or inhibited Gi to increase the cAMP concentration [81,82] and enhanced the cGMP generation via calcium/calmodulin-and nitric oxide synthase-dependent pathways [82], and the activation of G proteins by fluoride (1-20 mM, 19-380 mg/l) in smooth muscle cells initiated a series of events, including calcium mobilization, phospholipase C activation and protein kinase C activation [83,84]. At high concentrations sodium fluoride (600 mM, 11.4 g/l) inhibits also serine/threonine phosphatases [85].…”
Section: Activation Of G Proteins and Kinases And Inhibition Of Phospmentioning
confidence: 99%
“…Furthermore, in vitro studies show that DEX causes changes in PI metabolism. For example, Muraoka et al (1993) found that in vitro addition of DEX caused 5‐HT 2A receptor‐mediated Ca 2+ mobilization in C6 glioma cells, whereas Takahashi et al (1996) reported a decrease in norepinephrine‐stimulated PI metabolism after chronic DEX administration to rats. Recently, we observed that administration of DEX for 10 days caused a significant increase in [ 3 H]phorbol 12,13‐dibutyrate binding to PKC and in the immunolabeling of PKC γ and ε isozymes in rat cortex and hippocampus (Dwivedi and Pandey, 1998).…”
mentioning
confidence: 99%